Mith and Socium - Pavićević, Olivera (Zbornik Instituta za kriminološka i sociološka istraživanja, 2007)
The article is analyzing the connection between the social life of a community and mythic manifestations as a constitutive element of collective consciousness. The connection between the myth and ideology, and their manifestations in the periods of social crisis are being especially accentuated. Myth, and its more modern version – ideology, are represented as a "social magic" of a contemporary man. The building of artificial political myths is being analyzed through the changes in the function of language (semantic and magic use) and changes towards the collectivity oriented social responsibility – where the group emerges as a moral subject. Re-traditionalisation of social rituals and cults is represented as a framework for mythological reconstruction of reality.